Language Learning Strategies, Gender, and Motivation in Foreign Language Context - Yuniah Budiarti (Journal of English as A Foreign Language Teaching and Research, 2022)
How the students deal with their learning strategies has been investigated in the last few decades. The main points in this article focused on the profile of learning strategies used by the students of SMA N 16 Samarinda in the academic year 2020/ 2021 from the tenth to twelfth grade in learning English as a foreign language, gender, and motivation types. This study is quantitative research. The data was taken from two main questionnaires: SILL and motivation questionnaire. In analyzing the data, SPSS version 26 was used in this study. The number of participants was 99 students that consisting of 41 males and 58 females. The finding in this study found that the participants mostly used metacognitive strategies in their language learning and cognitive strategies were the least used. There was no significant difference between LLS usage with gender. Students’ intrinsic and intrinsic motivation play a significant role in their interest in learning English as a foreign language.